Integrated ag-data hub in Zambia using existing CIS platforms coupled with the iSAT and DEA data cube - Dhulipala, Ram; Moyo, Martin; Ngwira, Amos R; Rao, KPC; Amarnath, Giriraj; Homann, Sabine; Siamudaala, Victor; Chikoye, David (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report is divided into two parts (i) technical progress on building a prototype of the Agdatahub as well as generation and dissemination of advisories using iSAT (ii) governance mechanisms and stakeholder engagement to host Agdatahub.